The Fertilizer for Wellness Program and the Bean Market in Mexico - Borja-Bravo, Mercedes (2022)
Introduction. The Fertilizer for Wellness Program was implemented in Mexico since 2019 and seeks to increase the productivity of staple crops, including beans. Objective. To measure the effects of the Fertilizer for Welfare Program on the bean market in Mexico, the economic benefit that it will generate in society and its contribution to the food self-sufficiency of the grain. Materials and methods. A spatial equilibrium model that considered the bean producing and consuming regions in Mexico was formulated and validated, information in the average year 2017-2019 was used. Results. The results indicated that the national bean production and consumption would increase by 228 and 79 thousand tons if the Fertilizer for Wellness Program benefited all bean producers; the above would mean a 22.1 % increase in production that would allow lowering imports to zero. The Fertilizer for Wellness Program has promoted greater bean production and has contributed to food self-sufficiency by eliminating imports, in addition to generate economic benefits for society, as producer and consumer surpluses would increase by USD$ 429 million and USD$ 226 million. Conclusion. The Fertilizer for Wellness Program favored production growth and encouraged bean consumption in Mexico and discouraged bean imports; this action increased bean productivity and contributed to food self-sufficiency.